2017
DOI: 10.1371/journal.pone.0182599
|View full text |Cite|
|
Sign up to set email alerts
|

Association of whale sharks (Rhincodon typus) with thermo-biological frontal systems of the eastern tropical Pacific

Abstract: Satellite tracking of 27 whale sharks in the eastern tropical Pacific, examined in relation to environmental data, indicates preferential occupancy of thermo-biological frontal systems. In these systems, thermal gradients are caused by wind-forced circulation and mixing, and biological gradients are caused by associated nutrient enrichment and enhanced primary productivity. Two of the frontal systems result from upwelling, driven by divergence in the current systems along the equator and the west coast of Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…There was also considerable variation between individuals in the frequency of detections. One large female tagged at the Galapagos Islands surfaced off the shelf break of Peru after an interval of 4 months, which represents a movement consistent with that of other female R. typus that provided more frequent positions (Hearn et al 2013(Hearn et al , 2016Ryan et al 2017) and is related to thermal frontal systems instead of ocean current flow directions (but see Wilson et al 2006;Sleeman et al 2010). These results show that lengthy periods without transmissions do not necessarily imply tag shedding.…”
Section: Discussionsupporting
confidence: 51%
“…There was also considerable variation between individuals in the frequency of detections. One large female tagged at the Galapagos Islands surfaced off the shelf break of Peru after an interval of 4 months, which represents a movement consistent with that of other female R. typus that provided more frequent positions (Hearn et al 2013(Hearn et al , 2016Ryan et al 2017) and is related to thermal frontal systems instead of ocean current flow directions (but see Wilson et al 2006;Sleeman et al 2010). These results show that lengthy periods without transmissions do not necessarily imply tag shedding.…”
Section: Discussionsupporting
confidence: 51%
“…This possibility is intriguing given the evidence that thermoregulation is a strong driver of R . typus migration [67], vertical behavior [68], and physiology [69]. The Red Sea is thermally homogenous at depth with maximum surface temperatures of ~30°C and minimum temperatures at depth of ~22°C [70].…”
Section: Discussionmentioning
confidence: 99%
“…), while open ocean movements suggest utilization of prey concentrated by fronts (Ryan et al. ). Careful isotopic analyses of R. typus may thus be particularly informative for understanding and comparing diets in and outside aggregations, especially given the species’ threatened status and oceanic migrations which make lethal sampling and sustained feeding observations undesirable and difficult, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The diet of R. typus outside of coastal aggregations is generally unknown. Fatty acid analyses have suggested that they may depend on deep-water zooplankton and fishes during long-distance migrations (Rohner et al 2013, Marcus et al 2016, while open ocean movements suggest utilization of prey concentrated by fronts (Ryan et al 2017). Careful isotopic analyses of R. typus may thus be particularly informative for understanding and comparing diets in and outside aggregations, especially given the species' threatened status and oceanic migrations which make lethal sampling and sustained feeding observations undesirable and difficult, respectively.…”
Section: Introductionmentioning
confidence: 99%